Integration of Sectoral Policies: Potentials and Obstacles in a Complex and Interconnected World - Botah, Kwadwo Yeboah (Pencerah, 2023)
Over the past decade, a myriad of challenges such as climate change, food insecurity, flooding, drought, biodiversity loss, and inequalities have emerged across the global landscape. These problems are not only characterized by their complex origins and solutions but also embedded across multiple sectors, each with distinct agendas and uncertainties. Given this complexity, the concept of integrating policies across sectors has gained increased attention both politically and scholarly. Through a comprehensive review approach, this paper investigates the complex and multifaceted global challenges. It examines the role of sector-specific policies and the integration of these policies in addressing these challenges as well as obstacles to change. The findings underscore the existence of multiple complex and interrelated global challenges spanning many sectors with adverse national and local impacts. The paper revealed the substantial contributions of sectoral policies in confronting these intricate cross-cutting issues, while also highlighting their complexities. To overcome these challenges, the paper argues that the integration of sector-specific policies is central. By ensuring the integration of sectoral approaches, inconsistencies across sectors, fragmentation, and conflicts between policies are minimized. The paper contends that despite notable advances and recognition of policy integration, political commitment, complex application, and effective utilization are the primary challenges that need to be tackled to enjoy their full potential. The paper thus emphasized the need to establish efficient institutional machinery and unwavering political support for EPI. This strategic approach is essential to effectively confront the complex cross-cutting challenges, promote policy rationality and advance sustainable transformation.